Innate Immune Response to H3N2 and H1N1 Influenza Virus Infection in a Human Lung Organ Culture Model - Wu, Wenxin (2009)
We studied cytokine responses to influenza virus PR8 (H1N1) and Oklahoma/309/06 (OK/06, H3N2) in a novel human lung tissue model. Exposure of the model to influenza virus rapidly activated the mitogen activated protein kinase signaling (MAPK) pathways ERK, p38 and JNK. In addition, RNase protection assay demonstrated the induction of several cytokine and chemokine mRNAs by virus. This finding was reflected at the translational level as IL-6, MCP-1, MIP-1α/β, IL-8 and IP-10 proteins were induced as determined by ELISA. Immunohistochemistry for IP-10 and MIP-1α revealed that alveolar epithelial cells and macrophages were the source of these two cytokines. Taken together, both PR8 and OK/06 cause similar induction of cytokines in human lung, although OK/06 is less effective at inducing the chemokines MCP-1 and IL-8. This human organ culture model should thus provide a relevant platform to study the biological responses of human lung to influenza virus infection.